Ḍahīrah Ḥarakah Taṭbīq al-Sharī’ah al-Islāmīyah bi Cianjur: Dirāsah Tamhīdīyah - Tasman Tasman (Studia Islamika, 2005)
This piece focuses its attention on the process of 'the implementation of Islamic law in Cianjur' in West Java, in the local social-political context. The background to the ideology and concept of the implementation of Islamic law in Cianjur is a response to social and political developments both locally and nationally. Cianjur is a region which encourages and supports Gerakan Pembangunan Masyarakat Beraklakul Karimah (The Movement for the Development of a Society with Good Character) - often referred to as Gerbang Marhamah.DOI: 10.15408/sdi.v12i2.591